Recent advances in lignocellulosic biomass for biofuels and value-added bioproducts - A critical review - Ashokkumar, Veeramuthu; Venkatkarthick, Radhakrishnan; Jayashree, Shanmugam; Chuetor, Santi; Dharmaraj, Selvakumar; Kumar, Gopalakrishnan; Chen, Wei-Hsin; Ngamcharussrivichai, Chawalit (Bioresource technology, 2022)
[Display omitted] •Advanced pretreatment techniques focused on destruction of lignocellulosic biomass.•Recent genetic engineering approach in lignocellulose to bioproducts conversion.•Alternative biofuels synthesized from the lignocellulosic biomass was rationalized.•Explored high value bioproducts and biochemicals from lignocellulosic biomass.•Current techno-economic assessment considered for efficient biomass valorization. Lignocellulosic biomass is a highly renewable, economical, and carbon–neutral feedstock containing sugar-rich moieties that can be processed to produce second-generation biofuels and bio-sourced compounds. However, due to their heterogeneous multi-scale structure, the lignocellulosic materials have major limitations to valorization and exhibit recalcitrance to saccharification or hydrolysis by enzymes. In this context, this review focuses on the latest methods available and state-of-the-art technologies in the pretreatment of lignocellulosic biomass, which aids the disintegration of the complex materials into monomeric units. In addition, this review deals with the genetic engineering techniques to develop advanced strategies for fermentation processes or microbial cell factories to generate desired products in native or modified hosts. Further, it also intends to bridge the gap in developing various economically feasible lignocellulosic products and chemicals using biorefining technologies.